Pengetahuan dan Sikap Ibu Hamil Trimester III terhadap Pencegahan Covid-19 - Rosmala Dewi; Retno Widowati; Triana Indrayani (Health Information : Jurnal Penelitian, 2020)
The COVID-19 virus can be transmitted from person to person through coughing or saliva droplets. Pregnant women have a higher risk of morbidity and mortality than the general population. For this reason, knowledge of pregnant women regarding the prevention of COVID-19 is needed. The purpose of this study was to analyze the knowledge and attitudes of third trimester pregnant women towards the prevention of COVID-19. This research method used a cross sectional approach. The population in this study were 64 pregnant women in the city of Bandung with a sample of pregnant women who visited the Casa Medika Clinic. The research instrument was a questionnaire that was distributed online. The questions included 25 knowledge questions, 12 attitude questions and 10 preventive behavior questions. All questions on the questionnaire have been tested for validity and reliability. The results showed that out of 64 respondents, 56.3% of the respondents had a good prevention of COVID-19, 62.5% had good knowledge and 51.6% had a positive attitude towards preventing COVID-19. 19. There is a significant relationship between knowledge and prevention of COVID-19 in pregnant women. In this study, attitudes did not show a significant relationship with COVID-19 prevention behavior. Pregnant women are advised to maintain a positive attitude towards the prevention of COVID-19 in their daily life during the pandemic period, in order to avoid spreading COVID-19.